레이저 유속계를 이용한 2차원날개 단면 주위의 난류경계층 연구 - 안종우(J. W. Ahn); 이진태(J. T. Lee); 김기섭(K. S. Kim); 이창용(C. Y. Lee) (大韓造船學會 論文集, 1991)
The flow around a two-dimensional foil section Is measured by a LDV(Laser Doppler Velocimetry) system which is capable of measuring the datailed flow field without interfering the original flow field. A 2-color 3-beam LDV system, which is capable of mea,;tiring 2 velocity components simultaneously and uses 2W Ar-Ion laser source, is used to measure the flow field around an NACA0012 foil section. The measured flow velocities are analysed iii order to study the boundary layer characteristics, flow separation and the detail structure of the flow near the trailing edge of the foil. The boundary layer characteristics are compared with the results by the head's momentum integral method. For the case of small angle of attack at relatively higher Reynolds number, both results show good agreements. The measured data of the velocity field around an NACA0012 foil section would be valuable data to validate the CFD(Computational Fluid Dynamic) calculation results. The developed experimental technique to evaluate the characteristics of two-dimensional foil sections is essential tool to develope new blade sections which have good lift characteristics and better cavitation performances. 2차원 날개 단면 주위의 유동을 레이저 유속계측장치(LDV)를 이용하여 계측하였다. 레이저 유속계측장치는 주위 유동에 영향을 주지 않으면서 물체 주위의 유속을 정밀하게 계측할 수 있는 장비로서 본 논문에서는 2W Ar-Ion 레이져 광선을 이용한 2색 3선형 레이저 시스템을 사용하여 2방향 속도를 동시에 계측하였다. 레이저유속 계측장치를 사용하여 NACA0012 단면 주위의 유동을 계측한 후 난류경계층, 박리현상(Separation) 및 날개 뒷날에서의 유동 현상등에 대한 해석을 수행하였다. 계측된 유동장의 해석 결과를 Head의 운동량 적분법에 의한 계산결과와 비교하였다. 입사각이 작고 레이놀드수가 비교적 큰 경우에는 계측결과에 의한 경계층 특성과 운동량 적분법에 의한 계산결과가 잘 일치함을 보였다. 2차원 날개단면 주위 유동을 정밀 계측하여 수치계산 방법에 의한 결과와의 비교를 위한 유동계측 자료를 확보하였으며 캐비테이션 특징 및 양력특성이 우수한 새로운 날개단면 개발에 응용될 수 있는 2차원 단면시험법을 개발하였다.